Self-Fashioning and Ambiguities of Revolution in Austin Clarke’s "Initiation" - Vyas, Divyansh (Pivot: A Journal of Interdisciplinary Studies and Thought, 2023)
This is a paper on Austin Clarke’s short story from his collection of short stories titled, In This City. The story can be seen as being a part of Diaspora Studies, Immigrant Literature and Black Studies. The paper critically scrutinizes the short story based on the text and the context to argue how there was an absence of sustainable structures in the public sphere for black immigrant masculinities to sufficiently express themselves in a white heteronormative culture. Sociological ideas of Toby Miller and Erving Goffman are used to understand how black immigrant identities could only sufficiently be expressed in alternate sub-structures that remained isolated from the dominant white and heteronormative status quo. The central subject of “white space” of the issue is highly relevant to the paper’s exploration of how the systems of self-fashioning and revolution that exist in the public imagination are “incomplete” in their lack of reliability and sufficiency for black immigrants in Canada. Hence, their position in relation to aspirations of self-fashioning and revolution is one of ambiguity as the title of the paper itself states. The paper lays bare how these ambiguities are manufactured based on the chasm that exists between the ways in which the characters want to act and the ways of self-fashioning that society approves for them. It also explores how the systems of revolution are incomplete for them as there is an absence in terms of a revolutionary process that ensures stability and self-preservation.